2022
DOI: 10.1177/0145482x211072567
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life in People With Visual Impairments: A Systematic Review

Abstract: Objective This systematic review aimed to investigate the relationship between physical activity and quality of life (QOL) in people with visual impairments. Methods: Electronic searches were performed in PubMed, SPORTdiscus, CINAHL, Embase, and Web of Science. Observational studies describing the relationship between physical activity and QOL in adults with visual impairments were included. The Newcastle-Ottawa Scale (NOS) adapted for cross-sectional studies was used to assess the quality of the studies. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…We recently showed that people with VI are more likely to report improved quality of life when engaging in sufficient levels of physical activity [24]. However, evidence regarding physical activity and quality of life outcomes in people with VI is mostly from observational studies, and lacks on evaluate a specific type of activity, such as sports or non-sports activities [24]. Our data supports the hypothesis of a causal relationship between exercise practice and increased quality of life, particularly through the physical and environmental domains.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that people with VI are more likely to report improved quality of life when engaging in sufficient levels of physical activity [24]. However, evidence regarding physical activity and quality of life outcomes in people with VI is mostly from observational studies, and lacks on evaluate a specific type of activity, such as sports or non-sports activities [24]. Our data supports the hypothesis of a causal relationship between exercise practice and increased quality of life, particularly through the physical and environmental domains.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date on individuals with visual impairment generally focuses on children (Ball et al, 2022; Manista & Doikou, 2022; Philip et al, 2022) or older adults with visual impairment (Liu & Chang, 2020; Nastasi, 2020; Smallfield & Kadenberg, 2020). Little research addresses the lives of middle-aged persons with visual impairment (Caputo et al, 2022; Lund & Cmar, 2019) as services typically are provided upon onset of visual impairment at birth or as an older adult with age-related vision loss. Globally, there are over 2.2 billion people who are blind or visually impaired (World Health Organization, 2019).…”
Section: Introductionmentioning
confidence: 99%